2020
DOI: 10.20944/preprints202011.0324.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

<strong>Tracking Double-up Food Bucks (DUFB) Program Use Among Supplemental Nutrition Assistant Program (SNAP) Recipients and the Implications for Healthy Food Access</strong>

Abstract: Acceptance of SNAP benefits has increased in farmers&rsquo; markets (FM) over the years. However, getting SNAP recipients to take up the opportunity of extra dollars for healthy food options remains a challenge. Thus, we tracked the use of the Double-up Food Buck (DUFB) program among SNAP recipients who visit participating FMs in Utah to understand the unique characteristics of the program users. Our results identified varying types of program users (multiple and single market shoppers, more frequent and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…However, this result should be interpreted with caution because of the extremely small sample size. A previous study found that frequent FM shoppers received a larger quantity of DUFB tokens over the market season, which theoretically should result in larger F&V purchase and consumption [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this result should be interpreted with caution because of the extremely small sample size. A previous study found that frequent FM shoppers received a larger quantity of DUFB tokens over the market season, which theoretically should result in larger F&V purchase and consumption [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Throughout this paper, both NI and PPR projects will be collectively referred to as "healthy food financial incentive projects." There is growing evidence that supports the effectiveness of healthy food financial incentives on increasing participant FV intake and food security Atoloye & Durward, 2020;Moran et al, 2019;Parks et al, 2021) as well as support highlighting the economic benefits for local food economies and retailers Basu et al, 2013;Choi et al, 2017;Dimitri et al, 2015).…”
Section: Author Notementioning
confidence: 99%
“…Throughout this paper, both NI and PPR projects will be collectively referred to as "healthy food financial incentive projects." There is growing evidence that supports the effectiveness of healthy food financial incentives on increasing participant FV intake and food security (An, 2013;Atoloye & Durward, 2020;Moran et al, 2019;Parks et al, 2021) as well as support highlighting the economic benefits for local food economies and retailers (An, 2015;Basu et al, 2013;Choi et al, 2017;Dimitri et al, 2015).…”
Section: Healthy Food Financial Incentivesmentioning
confidence: 99%